Mykonos: a place of experimentation for the gastronomy-world relationship - Olivier Etcheverria (Via@)
The purchase of souvenirs is one of the activities realized by visitors as part of the tourist experience at a given destination. Among the many kinds of souvenirs offered around the world, food and beverages stand out for being goods charged with meanings linked to the geographic and touristic space, bearing attributes capable of generating sensations and extending the experience of the trip. Furthermore, as presents, they give to those who receive them a part of the lived experience, what we call a “gastronomic souvenir.” A wide range of products can be considered gastronomic souvenirs ; yet there are five variables that are fundamental for grasping the concept : foods and beverages ; identification ; packaging ; identity ; and transportability. From this presupposition, this study aimed to identify and analyze the commercialization of gastronomic souvenirs of Curitiba, an urban tourist destination located in the southern region of Brazil. Empirical and exploratory in nature, the case study began with a bibliographic review followed by field work aiming to identify the foods and beverages sold in establishments marketing souvenirs, data being collected from a spatial sample delineated by the circuit of the Linha Turismo (Tourist Line), a tourism bus service in the city. As a result, we found that the offer of gastronomic souvenirs in Curitiba is varied, though cookies, chocolates, wines and cane alcohol (cachaça) stand out, as these are tied to the cultural identity of Curitiba and the region in which the city is inserted.